2015
DOI: 10.3892/ol.2015.3493
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphoma with uncommon clinical manifestations: A case report

Abstract: Abstract. Extranodal lymphoma occurs in ~40% of all patients with lymphoma and has been described in virtually all organs and tissue. However, diffuse large B-cell lymphoma (DLBCL), which is the most common histological subtype of non-Hodgkin's lymphoma (NHL), primarily arising in the retroperitoneal region has been rarely reported. Primary retroperitoneal lymphoma without renal or ureteral involvement affecting the genitourinary system has not been reported until now. In this article, we report the rare case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Cai et al have reported a case of a girl child who was diagnosed with primary DLBCL in the retroperitoneal as well as gastrointestinal regions at the same time. Renal colic was the initial indication of this condition, which was unusual [ 6 ]. Remnants of the thymus are often found in the mediastinal mass, and this may lead to a mistaken diagnosis of thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al have reported a case of a girl child who was diagnosed with primary DLBCL in the retroperitoneal as well as gastrointestinal regions at the same time. Renal colic was the initial indication of this condition, which was unusual [ 6 ]. Remnants of the thymus are often found in the mediastinal mass, and this may lead to a mistaken diagnosis of thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…About 30%–40% of all NHL cases arise from sites other than lymph nodes, spleen, or bone marrow. 1,2,8 They may also arise from sites typically devoid of lymphocytes. Almost half of all ENL cases reported had DLBCL histology.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal involvement may also be due to the regional spread of nodal disease or hematogenous dissemination. 1,2,8 Primary skeletal muscle NHL of diffuse large B-cell immunophenotype is exceptionally rare (incidence rate of 0.1%-0.5% in all extranodal lymphoma (ENL) of the extremities). [5][6][7] However, diffuse large B-cell lymphoma (DLBCL), which is the most common histological subtype of NHL, primarily arising in the retroperitoneal region, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Also, several cases of diffuse large B-cell lymphoma have been reported. [3,4] Non-Hodgkin lymphoma is now classified according to WHO classification in which lymphomas are roughly classified into B, T, NK, null, lymphoblastic, and unclassifiable lymphomas. [5][6][7][8][9][10][11][12][13] Primary indolent B-cell lymphoma is a category of B-cell lymphoma comprising of follicular lymphoma, mantle cell lymphoma, lympho-plasmacytic lymphoma, mucosa-associated lymphoid tissue (MALT) lymphoma, and small lymphocytic lymphoma/chronic lymphocytic lymphoma.…”
Section: Introductionmentioning
confidence: 99%